Respuesta :
(x-3)(3x+7)=0
x-3=0 or 3x+7=0
1. x-3=0
x₁=3
2. 3x+7=0
3x=-7
x₂=-7/3 = -2(1/3)
x-3=0 or 3x+7=0
1. x-3=0
x₁=3
2. 3x+7=0
3x=-7
x₂=-7/3 = -2(1/3)
Answer:
The values of x is, [tex]3[/tex] or [tex]\frac{-7}{3}[/tex].
Step-by-step explanation:
[tex](x - 3) (3x + 7) = 0[/tex]
Using Zero Factor principle:
Since the factors are in the factorize form and their product is equal to zero.
so, equate each factor equals to zero and solve for the values of x.
then, [tex](x-3)=0[/tex] ⇒[tex]x=3[/tex]
and [tex](3x+7)=0[/tex] ⇒[tex]x=\frac{-7}{3}[/tex]
Therefore, the values of x is, [tex]3[/tex] or [tex]\frac{-7}{3}[/tex].